KOMPENSASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI RESTORAN KAMPOENG DAUN - Moch Fachri Supriyadi; Sidik Priadana; Bayu Indra Setia (Jurnal Riset Bisnis dan Manajemen, 2017)
The aim of this research is to understand and analyze how compensation and working discipline give impact to the job satisfaction in Restaurant Kampoeng Daun Kabupaten Bandung Barat. Samples were employees at Restaurant Kampoeng Daun which amounts to 60 respondents. This research uses a quantitative approach, data were collected by questionnaire. The data analysis technique used is multiple linear regression analysis. As seen on descriptive analysis, can be seen compensation, working discipline and job satisfaction were catagorized effecvtive. The result of verification analysis shown that compensationin and work discipline have a significant effect to job satisfaction of 66,9%.. Partially, the compensation effect on job satisfaction at 35.4% and working discipline by 31,5%.